Zoonotic and Public Health Implications of Campylobacter Species and Squamates (Lizards, Snakes and Amphisbaenians) - Masila, Nicodemus M. (Pathogens, 2020)
Campylobacter spp. is one of the most widespread infectious diseases of veterinary and public health significance. Globally, the incidence of campylobacteriosis has increased over the last decade in both developing and developed countries. Squamates (lizards, snakes and amphisbaenians) are a potential reservoir and source of transmission of campylobacteriosis to humans. This systematic review examined studies from the last 20 years that have reported squamate-associated human campylobacteriosis. It was found that C. fetus subsp. testudinum and C. fetus subsp. fetus were the most common species responsible for human campylobacteriosis from a squamate host. The common squamate hosts identified included bearded dragons (Pogona vitticeps), green iguana (Iguana iguana), western beaked gecko (Rhynchoedura ornate) and blotched blue-tongued skink (Tiliqua nigrolutea). People with underlying chronic illnesses, the immunocompromised and the elderly were identified as the most vulnerable population. Exposure to pet squamates, wild animals, consumption of reptilian cuisines and cross contamination with untreated water were risk factors associated with Campylobacter infections. Proper hand hygiene practices, responsible pet ownership, ‘One Health’ education and awareness on zoonotic diseases will help reduce the public health risks arising from Campylobacter exposure through squamates. Continued surveillance using molecular diagnostic methods will also enhance detection and response to squamate-linked campylobacteriosis.